Malaysian French Foreign language learners’ perception on their Speaking Ability at Tertiary level - Berbiche Mariama; Asmaa AlSaqqaf; Suyansah Swanto; Roseni Ariffin; Alpha Bodian (IJHS, 2018)
Malaysian government has attached great importance to proficiency in a third language in theMalaysian education system, especially at the tertiary level. The aim is to develop human capital that cancompete in the international arena and contribute significantly in the socio-economic development of thecountry. Large resources have been poured into foreign language (FL) teaching in the Malaysianuniversities. Unfortunately, students continue to graduate with unsatisfactory proficiency in the thirdlanguage. A case in point is the French as Foreign Language (FFL) undergraduates. Students are generallynot able to communicate in the target language (TL). This study was conducted to find out, FFL learner’sperceptions on their speaking proficiency. The study also intended to find out the changes that mightcontribute, based on their perceptions, to develop their speaking proficiency in French. A surveyquestionnaire was used to collect data from 100 tertiary education students from Universiti Malaysia Sabah(UMS). The finding of the study indicated that FFL learners are not able to communicate in the TL due tothe limited exposure to the French language in and outside the classroom, the FFL learners’ attitude towardsFrench as a foreign language, the FFL teachers behaviour and the French foreign language curriculum andtextbook.